Pengaruh Waktu Reaksi Pembuatan Biodiesel dari Minyak Jelantah dengan Bantuan Katalis Bassa NaOH terhadap Sifat Fisika dan Kimia Produk Biodiesel - Eka Megawati; Debora Ariyani; I Ketut Warsa; Junety Monde; Sapril Sapril; Amirul Mukminin (Journal on Education, 2023)
The effect of the transesterification reaction time of 0.6% mass % NaOH catalyst in the formation of methyl ester (biodiesel) made from used waste cooking oil as raw material 6 times usage and methanol 1: 5 mass has been studied at 60°C. The reaction times used were 30, 40, and 45 minutes. All samples resulting from the transesterification reaction have been studied for their chemical and physical properties. Parameters of chemical properties included in the Indonesian National Standard (SNI) for all samples were % FFA, pH, while the water content was above the SNI standard. The physical property parameters for all samples that meet SNI are only flash point, color and 90% distillation. While the density of all test samples was lower than the SNI which was set at 850-890 Kg/m3, the results obtained for reaction times of 30, 40 and 45 minutes were 828, 833 and 836 Kg/m3 respectively. The highest yield was owned by a reaction time of 40 minutes, namely 80%. As for the reaction time of 35 and 45 minutes respectively 79 and 65%.